Do Place‐Based Policies Promote Sustainable Development? A Study Based on Resource‐Exhausted Cities in China. - Li, Chaowei; Hong, Tao; Ma, Tao; Yang, Hang (Kyklos, 2025)
The transformation of resource‐exhausted cities is of great significance to the sustainable development of the region, but the effect of supportive policy for resource‐exhausted cities has yet to be examined. This study empirically analyzes the impact of the supportive policy on industrial transformation based on prefecture‐level data in China from 2006 to 2012 using time‐varying difference‐in‐differences. This study finds that the supportive policy increases urban per capita GDP but has a negative effect on the proportion of tertiary industry and passes a series of robustness tests. Further analysis shows that the negative effect has a dynamic effect and becomes more significant in cities with stronger local government capacity and higher marketization level. Mechanism analysis reveals that the policy influences industrial transformation by affecting innovation, capital allocation, and labor allocation. This results reveals the existence of the "resource curse amplification" effect of policies, provides empirical support for the conditional resource curse theory, and challenges the static inevitability of the "resource curse." Additionally, it also re‐examines the relationship between the government and the market, reveals the potential risks of "government‐led transformation," which echoes the paradox of state capacity, and enriches research on place‐based policy.